The impact of performance appraisal on job performance among employees at Perbadanan Kemajuan Negeri Melaka, 2007 / Noorhafezah Md Noor - Md Noor, Noorhafezah (Faculty of Business and Management, 2008)
Purpose – There are four purposes to this research. First, to identify the tools that company use to evaluate their staff. Second, to identify the important of performance appraisals towards staffs’ performance. Third, to identify the effectiveness of performance appraisals towards staff’s performance and the organization achievement. And lastly, to identify the staff’s satisfaction after performance appraisal process. Design/Methodology – The type of research is Descriptive Research, which is conducted to discover and determine the characteristics of a population. It seeks to determine the answer to the questions of who, what, when, where and how. Data gathered from questionnaires, interviews and observations. Sample size is 50 for this research. Finding – There were an impact of performance appraisals on job performance. Performance appraisal is a step to know how well employees’ job performance based on the results of performance appraisal. This study is more to know the good impact from performance appraisal system. Managers can use performance appraisal information in four ways. There are motivation, personnel movement, training and feedback for improvement and personal development. Research limitations – This study was conducted with 50 sample size from the population. Each staff has different feedback in answering the questionnaire so it gives impact to this study. Practical Implication - Study results show that performance appraisal needs to analysis and further study on their feedback. The study needs on how to improve or eliminating the weaknesses or dissatisfaction by employees on performance appraisal system in evaluating employees’ job performance.